Rancang Bangun Alat Timer Otomatis Pesawat Atwood Berbasis Arduino - Geraldo Frits Elias; Tineke Makahinda; Jimmy Lolowang (Charm Sains: Jurnal Pendidikan Fisika, 2022)
This research was motivated by the problem of accuracy measuring the Atwood machine practicum time caused by the time lag when activating and pausing the stopwatch. The purpose of this research is to produce a practical tool for measuring time, namely an Arduino-based automatic timer that is suitable for use in practical activities in the UNIMA physics laboratory. This research is a research and development model of the ADDIE model which consists of several stages of research, namely analysis, design, development, implementation, evaluation, finishing of media products. Data collection was carried out by experiment, expert/expert validation. The results of testing the Arduino-based automatic stopwatch tool have a gravity value of 10.095 m/s2 and an error percentage of 2.7% to 3.4% while the validation of material experts and media experts for Atwood aircraft practicum tools and guides using an Arduino-based automatic timer is at criteria 90.4% - 95.2% and the assessment given by a small group is 98.8%. Based on the results of the study, it can be concluded that tools and guides have been produced for time with valid or appropriate qualifications.s.